Role of Anopheles gambiae s.s. and Anopheles coluzzii (Diptera: Culicidae) in Human Malaria Transmission in Rural Areas of Bouaké, in Côte d'Ivoire. Issue 4 (26th January 2020) - Zoh, Dounin D; Yapi, Ahoua; Adja, Maurice A; Guindo-Coulibaly, Négnorogo; Kpan, Didier M S; Sagna, André B; Adou, Arsène K; Cornelie, Sylvie; Brengues, Cécile; Poinsignon, Anne; Chandre, Fabrice
Abstract: Studies done in Bouaké (Côte d'Ivoire) about 20-yr ago reported that Anopheles gambiae s.l. Giles was the major malaria vector. The present study aimed to update these data and to identify the main vectors. Mosquitoes were collected in Allokokro and Petessou villages between June 2014 and December 2015 using the human landing catching method. Potential breeding sites of An. gambiae s.l. were identified in August and October 2014 and mapped using GPS. Anopheles species were morphologically and molecularly [polymerase chain reaction (PCR)] identified. Ovaries of female were dissected to determine the parity and infection with Plasmodium was detected in head and thorax by quantitative PCR. In Allokokro, the biting rate of An. gambiae s.s was significantly greater than Anopheles coluzzii, whereas, in Petessou, biting rates of both species were comparable. Plasmodium falciparum (Haemosporida: Plasmodiidae), Plasmodium malariae (Haemosporida: Plasmodiidae), and Plasmodium ovale (Haemosporida: Plasmodiidae) identified in both villages. The infection rates of An. gambiae s.s . and An. coluzzii were not significantly different. The entomological inoculation rate (EIR) of An. gambiae s.s. for P. falciparum was 9-fold greater than that of An . coluzzii in Allokokro; however, in Petessou, the EIRs of both species were comparable. In both village, An. gambiae s.s was responsible for P. falciparum and P. ovale transmission whereas An. coluzzii transmitted all three Plasmodium species.